1979
DOI: 10.1111/j.1365-3083.1979.tb02717.x
|View full text |Cite
|
Sign up to set email alerts
|

Lymphoblastoid Cell Lines are Polyclonal Activators of Human T Lymphocytes

Abstract: Following stimulation with autologous or allogeneic lymphoblastoid cell lines (LCL) human T lymphocytes acquire two properties which suggest that LCL act as polyclonal activators. Cytotoxic activity, which has an antigen-specific component, is produced towards normal lymphocytes and LCL, and the cells become capable of mounting proliferative responses to antigens on human B lymphocytes which have accelerated secondary-type kinetics. Only weak responses to autologous cells occur. In addition, repeated restimula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1981
1981
1984
1984

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 17 publications
(10 reference statements)
0
2
0
Order By: Relevance
“…There are several possible explanations for these anomalous patterns of killing. Firstly, variation in the experimental format may be vital in determining the outcome of the T-cell response to challenge with autologous LCL; high doses of stimulator cells may lead to a non-specific or polyclona1 T-cell response (Svedmyr et al, 1975;Boylston and Anderson, 1979), whereas low levels of stimulation may induce a specific response, as shown in this study. Moreover, clones of specific cytotoxic T cells may be selected and enriched by continual restimulation .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…There are several possible explanations for these anomalous patterns of killing. Firstly, variation in the experimental format may be vital in determining the outcome of the T-cell response to challenge with autologous LCL; high doses of stimulator cells may lead to a non-specific or polyclona1 T-cell response (Svedmyr et al, 1975;Boylston and Anderson, 1979), whereas low levels of stimulation may induce a specific response, as shown in this study. Moreover, clones of specific cytotoxic T cells may be selected and enriched by continual restimulation .…”
Section: Discussionmentioning
confidence: 95%
“…Another aspect of the AMLR which has been investigated in detail is the cytotoxic response by T cells to autologous Epstein-Barr virus (EBV)-transformed lymphoblastoid cell lines (LCL). There are numerous reports showing that autologous LCL stimulated the generation of broadly non-specific cytotoxic T cells (Svedmyr et al, 1975;Viallat et al, 1978, a, b ;Vande Stouwe et al, 1977;Miller et al, 1979;Biron et al, 1981), and Boylston and Anderson (1979) have indicated that LCL are polyclonal activators of human T lymphocytes. In contrast, Sugamura and Hinuma (1980), using multiply-restimulated cells from EBVseropositive donors, concluded that two effector cell populations were generated, one EBV-specific and one non-specific.…”
mentioning
confidence: 99%